Assessing Lead Waste and Secondary Resources in Major Consumer Nations: A Vanishing Resource or a Toxic Legacy? - Sebastien M. R. Dente; Jian Zhang; Seiji Hashimoto (Resources)
This study applies a dynamic material flow analysis to track lead flows, in-use stocks, secondary reserves, and recycling trends across eleven major economies from 1950 to 2018. The results show the global lead cycle has shifted from a variety of industrial applications to a predominant reliance on lead–acid batteries. By 2018, China had become the dominant actor, accounting for 82% of global lead extraction and holding 47% of total in-use stocks (58.3 Mt). Despite regulatory efforts to phase out dissipative uses, the global domestic processed output in 2018 reached 1429 kt, surpassing 1976 levels (1148 kt). At the same time, end-of-life lead waste increased to 7717 kt, yet only 48% was successfully recovered, exposing inefficiencies in current recycling and circular economy initiatives. Secondary reserves also varied widely, with China (18.5 Mt) and the US (9.9 Mt) leading in absolute terms, while Europe maintained the highest per capita reserves. The growing competition from lithium-ion batteries raises questions about the long-term role of lead in industry. If demand declines, the accumulation of unmanaged legacy stocks could become a significant environmental challenge. To address these issues, improvements in recycling systems, stricter waste management policies, and the development of sustainable alternatives are needed.